Burns challenges - A social media dictated phenomena in the younger generation - Verena Chu; Ardit Begaj; Lopa Patel (Elsevier, 2018)
Background and aim: 'Burns challenges' leading to battle scars are a current youth culture phenomenon propagated by social media. Platforms such as YouTube, Twitter and Facebook have been noted to show adolescents perform these challenges resulting in an increasing incidence of flame, friction or chemical burns of varying severity. Methods: Aim: A literature review was performed on PubMed, READ, Epistemonikos with key search criteria including challenges, fire, deodorant, ice and salt and eraser burns. References on each challenge were researched on social media platforms and generic search engines were used to review all public availability on these challenges. Results: The search resulted in nine articles between 2012 and 2016. Further searches on Google, typing in the mode of challenge as the keyword, produced case reports. Ages of those involved normally ranged from 10 to 20 with one patient aged 8.5 and another 45. Available YouTube videos regarding the eraser challenge, deodorant challenge, ice and salt challenge and fire challenge were quoted as 320,000, 155,000, 939,000 and 24,800,000 respectively. Some videos had age restrictions in place, but the majority of videos uploaded by younger YouTubers (children) had no age restrictions and was allowed to remain on YouTube. Conclusion: Creative ways to demonstrate stealth by performing these burns injuries is a common occurrence and correlates to a rising incidence of these burns. Methods of social media clearly fuel this by publicising events. It is important to be vigilant in identifying this aetiology of burn injury, not to confuse it with non-accidental injury or psychotic deliberate self-harm, and to educate patients of the long-term consequences. Further studies should be done into understanding the significant influence social media has on risky behaviours in children and adolescents, and the general public, especially social media sites, should be educated on the extent of harm these challenges have so that hosting of these videos and contents can be better regulated. Keywords: Burn challenge, Ice salt challenge, Eraser challenge, Deodorant challenge, Social media, Children adolescent risky behavior